2007
DOI: 10.1159/000103291
|View full text |Cite
|
Sign up to set email alerts
|

Aortico-Right Ventricular Tunnel: Prenatal Diagnosis Leading to Neonatal Survival

Abstract: In the 36th week of gestation a large aortico-right ventricular tunnel with an otherwise structurally normal heart was diagnosed by fetal echocardiography. This report describes for the first time the impact of the timely prenatal diagnosis of an aortico-right ventricular tunnel followed by successful management in early infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Although more than 130 cases of aorto-left ventricular tunnel have been reported, aorto-right ventricular tunnel (ARVT) is a rare entity and only 14 cases have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This condition presents early in life with an obligatory left to right shunt. 15 We report our experience of successful surgical management of two cases of ARVT with associated coronary artery anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more than 130 cases of aorto-left ventricular tunnel have been reported, aorto-right ventricular tunnel (ARVT) is a rare entity and only 14 cases have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] This condition presents early in life with an obligatory left to right shunt. 15 We report our experience of successful surgical management of two cases of ARVT with associated coronary artery anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 14 cases, nine were associated with a coronary artery anomaly of either an absent right 6,13 or left coronary ostium 2 or origin of any one of the coronary arteries from the tunnel. 1,4,[9][10][11][12] Poptani et al reported a case of ARVT with a single coronary artery arising away from the tunnel. 13 The review of previous reports clearly shows a frequent association of coronary artery anomaly with ARVT which happens to be more than a chance finding and may suggest a possible embryologic basis for the origin of this anomaly.…”
Section: Discussionmentioning
confidence: 99%
“…Large congenital coronary cameral fistulae (CCCF) are very rare congenital malformations that belong to the group of coronary artery fistula's (CAF) . The anatomy is particular to each fistula .…”
Section: Introductionmentioning
confidence: 99%
“…Large congenital coronary cameral fistulae (CCCF) are very rare congenital malformations that belong to the group of coronary artery fistula's (CAF) . The anatomy is particular to each fistula . The main sites of origin of CCCF's are the right coronary artery (RCA) (55%), left coronary artery (LCA) (35%), or both main coronary arteries (10%) and the main termination site is the right ventricle (RV) (40%) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation